2015
DOI: 10.1186/s12931-015-0305-4
|View full text |Cite
|
Sign up to set email alerts
|

The whole - genome expression analysis of peripheral blood mononuclear cells from aspirin sensitive asthmatics versus aspirin tolerant patients and healthy donors after in vitro aspirin challenge

Abstract: BackgroundUp to 30 % of adults with severe asthma are hypersensitive to aspirin and no unambiguous theory exists which provides a satisfactory explanation for the occurrence of aspirin-induced asthma (AIA) in some asthmatic patients. Therefore, the aim of this study was to compare the AIA expression profile against aspirin tolerant asthma (ATA) and healthy volunteers (HV) profile in peripheral blood mononuclear cells (PBMCs) after in vitro aspirin challenge in Caucasian population.MethodsPBMCs were separated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…In particular, expression of CNPY3 and FOSL1 were significantly lower in AIA vs healthy controls, while ERAS expression was increased. Protein expression of FOSL1 in PBMCs was also significantly lower for AIA than the control groups 75 . While the study lacked mechanistic investigation of these novel candidate genes for AERD, the authors suggest these genes could participate in innate immune response pathways and pathways for tissue/cell remodeling and airway hyperresponsiveness that contribute to the pathogenesis of AERD 75 .…”
Section: Update On the Genetics Of Aerdmentioning
confidence: 87%
See 1 more Smart Citation
“…In particular, expression of CNPY3 and FOSL1 were significantly lower in AIA vs healthy controls, while ERAS expression was increased. Protein expression of FOSL1 in PBMCs was also significantly lower for AIA than the control groups 75 . While the study lacked mechanistic investigation of these novel candidate genes for AERD, the authors suggest these genes could participate in innate immune response pathways and pathways for tissue/cell remodeling and airway hyperresponsiveness that contribute to the pathogenesis of AERD 75 .…”
Section: Update On the Genetics Of Aerdmentioning
confidence: 87%
“…Comparing gene expression and whole genome sequence profiles from AERD cases and non-AERD asthmatics or healthy controls using whole-genome microarray expression profiling and next-generation sequencing methods provides a discovery-based approach to interrogate mRNA transcripts across the genome with specific correlation to the phenotype. A combined approach utilizing microarray expression profiling and a candidate gene analysis in PBMCs from a small Caucasian population identified three genes with expression profiles that significantly differed between AIA vs. ATA and/or AIA vs. healthy subjects 75 . In particular, expression of CNPY3 and FOSL1 were significantly lower in AIA vs healthy controls, while ERAS expression was increased.…”
Section: Update On the Genetics Of Aerdmentioning
confidence: 99%
“…Through transcriptome-wide association studies, transcription factor RERE was identified as a candidate causal gene of asthma 41 . The whole-genome expression analysis of peripheral blood mononuclear cells indicated that FOSL1 was positively associated with aspirin-intolerant asthma 42 . In addition, miR-20a epigenetically regulated the IL-10 production by targeting HDAC4 and attenuated allergic inflammation in the human mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the FOSL1/AP-1 transcription factor, it regulates gene expression in human lung epithelia ( Elangovan et al, 2018 ). mRNA expression of FOSL1 was shown to be decreased in PBMCs of aspirin-intolerant asthma ( Kacprzak et al, 2014 ; Wieczfinska et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%